2022
DOI: 10.1021/acs.molpharmaceut.2c00083
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Temozolomide-Conjugated Gold Nanoparticle Photothermal Therapy of Drug-Resistant Glioblastoma and Its Mechanism Study

Abstract: Temozolomide (TMZ) is a standard-of-care chemotherapeutic drug for the treatment of glioblastoma (GBM), but TMZ-acquired resistance limits its therapeutic effect. In this study, TMZ-loaded gold nanoparticles (TMZ@GNPs) with anti-EphA3 modification on the surface (anti-EphA3-TMZ@GNPs) were synthesized for chemical and auxiliary plasma photothermal treatment (GNPs-PPTT), aiming to overcome the problem of glioma resistance to TMZ and improve the therapeutic effects of GBM. The prepared anti-EphA3-TMZ@GNPs were sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…This photothermal treatment prolonged the survival time of the GBM xenograft model by 1.64-fold compared to free TMZ. 192 In another study on the intranasal administration of TMZ, Au NPs were coated with methoxy polyethylene glycol (mPEG)-detachable (d)-polyethyleneimine (PEI) (Au@PP), and then electrostatic interactions with polyinosinicpolycytidylic acid ( poly(I:C)) were induced. The in vivo study on C57BL/6 mice bearing an intracranial GBM tumor demonstrated that Au@PP/poly(I:C) induced type I interferon (IFN-I) expression after endocytosis into GBM cells, and significantly accumulated in the glioma tissue after intranasal administration, and AuNPs@PP/poly(I:C) plus TMZ remarkably enhanced the overall survival of the mice in comparison with the free TMZ group.…”
Section: Review Biomaterials Sciencementioning
confidence: 99%
“…This photothermal treatment prolonged the survival time of the GBM xenograft model by 1.64-fold compared to free TMZ. 192 In another study on the intranasal administration of TMZ, Au NPs were coated with methoxy polyethylene glycol (mPEG)-detachable (d)-polyethyleneimine (PEI) (Au@PP), and then electrostatic interactions with polyinosinicpolycytidylic acid ( poly(I:C)) were induced. The in vivo study on C57BL/6 mice bearing an intracranial GBM tumor demonstrated that Au@PP/poly(I:C) induced type I interferon (IFN-I) expression after endocytosis into GBM cells, and significantly accumulated in the glioma tissue after intranasal administration, and AuNPs@PP/poly(I:C) plus TMZ remarkably enhanced the overall survival of the mice in comparison with the free TMZ group.…”
Section: Review Biomaterials Sciencementioning
confidence: 99%
“…Moreover, PTT as well as SDT have been used in the treatment of various cancers and bacterial drug resistance, and all of them have obtained better treatment results. [13][14][15][16] Some researchers have prepared temozolomidecoupled gold nanoparticles with photothermal therapeutic effects to overcome temozolomide resistance in glioma and improve the therapeutic effect of glioma. 13 Similarly, multidrug resistance in gastric cancer can be reversed by using DOX-loaded nanoparticles with sonodynamic therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Some researchers have prepared temozolomidecoupled gold nanoparticles with photothermal therapeutic effects to overcome temozolomide resistance in glioma and improve the therapeutic effect of glioma. 13 Similarly, multidrug resistance in gastric cancer can be reversed by using DOX-loaded nanoparticles with sonodynamic therapeutic effects. 17 There are currently very few studies utilizing physical approaches to cure drug resistance in lung cancer, despite PTT using multifunctional CuO/Cu 2 O nanocubes having been reported to treat multidrug-resistant lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…TMZ also has some deficiencies, including inferior tumor targeting, considerable toxicities or adverse effects, drug resistance via DNA repair, and the regulation of several signaling pathways. The therapeutic effect of GBM remains unsatisfactory, even though timely operation and postoperative CT ( Yu et al, 2022 ). GBM remains a challenging and valuable research topic.…”
Section: Introductionmentioning
confidence: 99%